THE PETROPHYSICAL APPRAISAL OF ISOLATING PROPERTIES THE MAJOR ZHYTOMYR GRANITOIDS TYPES OF THE VOLYN REGION OF THE UKRAINIAN SHIELD - Kuziv, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The petrophysical estimation of some physical characteristics of penetrability the major zhytomyr granitoids types of the Volyn region the Ukrainian Shield was made.